Public health failure in the prevention of neural tube defects: time to abandon the tolerable upper intake level of folate - Nicholas J. Wald; Joan K. Morris; Colin Blakemore (Frontiers Media S.A., 2018)
Abstract The neural tube defects anencephaly and spina bifida are two of the most common serious congenital malformations. Most cases can be prevented by consuming sufficient folic acid immediately before pregnancy and in early pregnancy. Fortification of flour with folic acid to prevent these defects has been implemented in 81 countries without public objection or indication of harm. An obstacle to the wider adoption of fortification arises from the creation of a "tolerable upper intake level" for folate (which includes natural food folate as well as synthetic folic acid), and which has been set at 1 mg/day, thereby proscribing higher folate intakes. Increasing the intake of folic acid in a population will necessarily increase the number of people with a folate intake greater than 1 mg per day, and this concern is obstructing folic acid fortification. This paper shows that the scientific basis for setting any upper limit, let alone one at 1 mg/day, is flawed. An upper intake level is therefore unnecessary and should be removed, thus allaying unjustified concerns about folic acid fortification. As a result, the full global opportunity to prevent two serious fatal or disabling disorders can and should be realized.